Short-term cytotoxicity of zinc oxide nanoparticles on Chlorella vulgaris - Sinouvassane Djearamane,; Wong, Ling Shing; Lim, Yang Mooi; Lee, Poh Foong (Penerbit Universiti Kebangsaan Malaysia, 2019)
Zinc oxide nanoparticles (ZnO NPs) are widely used in industrial and personal care products. The use of these nanoparticles (NPs) has created residues that contaminate the environment, thus cytotoxicity studies of the NPs in biological system is required. Most of the recent cytotoxicity studies has however focused on long-term exposure of the NPs to the biological system. In this study, the cytotoxicity effects of short-term exposure of ZnO NPs to Chlorella vulgaris are reported. The algal cells were exposed to 10, 50, 100, 150, and 200 mg/L of ZnO NPs for 12 h. The toxicity effects of ZnO NPs were then determined through the changes in fluorescence emission of chlorophyll, algal biomass and the viable cell count. The results showed a decrease in the chlorophyll content, algal biomass and cell viability after treatment with ZnO NPs as compared with control. Through this study, the effects of ZnO NPs to C. vulgaris were confirmed. The significant responses of the algal cells to ZnO NPs in a short duration of exposure reflect the potential of the algal cells to be used as bioindicators of ZnO NPs in the aquatic environment.